Cross-sectional analysis of physical activity in 2-4-year-olds in England with paediatric quality of life and family expenditure on physical activity - Laura Tinner; Ruth Kipping; James White; Russell Jago; Chris Metcalfe; William Hollingworth (BMC, 2019)
Abstract Background Many children do not meet the recommended level of daily physical activity, even with the widely acknowledged health benefits associated with being physically active. There is a need to establish factors related to physical activity in children so that public health interventions may be appropriately designed. We investigated the association between Pediatric Quality of Life Inventory (PedsQL), family expenditure on physical activity and objectively measured daily physical activity in 2-4-year-old children. Methods Cross-sectional study with a sample of 81 UK preschool children taking part in the NAPSACC UK feasibility randomized controlled trial. Descriptive statistics are presented. We undertook Student t-tests to establish differences in physical activity by gender, age, parental education and nursery versus non-nursery days. Mixed effects linear regressions were used to model the association between minutes spent physically activity, minutes spent in moderate-to-vigorous (MVPA) physical activity and PedsQL scores (physical and psychosocial) and family expenditure on physical activity. Results Most children (88.9%) did not engage in the recommended 180 min daily physical activity. There was mean (SD) of 141.9 (33.1) daily minutes of physically activity and 22.2 min per day (SD = 9.9) of MVPA. Boys and older children were more physically active. Children were more active on nursery days. There was no difference in physical activity by parental education. Half of the sample parents (50.6%) spent less than £9.00 weekly on their pre-schooler's physical activity. Children within the highest tertile of PedsQL physical functioning scores had higher levels of MVPA (3.6, 95% CI: − 1.3-8.4, p-value 0.15), although confidence intervals crossed the null in the adjusted model. We found no evidence of an association between positive PedsQL psychosocial scores, or higher parental expenditure on physical activity, with the physical activity variables. Conclusions Children in this sample were not meeting the recommended 180 min of daily physical activity. The 2-4-year-olds were most active on nursery days. There is no evidence of an association between better PedsQL physical scores and higher levels of MVPA. There was no evidence of an association between expenditure on physical activity and time spent physically active. Further examination in larger representative datasets is needed.